PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP LOYALITAS MITRA MELALUI KEPUASAN MITRA (Studi Pada Mitra Leker Joker Corporation di Yogyakarta) - Qurrota Ayun; Sri Suryoko (Universitas Diponegoro, 2020)
In order to get loyal customers, many companies produce products that are more unique and of high value, in order to win the competition. Joker Corporation as one of the companies engaged in the field of food and beverage will always create delicious, innovative, unique, interesting and up-to-date products to create partner loyalty. However, from 735 leker partners scattered in various regions in Indonesia since 2013, there are currently only 30 active partners, namely partners who are still re-buying raw materials and complement of joker leker from Joker Corporation. This indicates the quality of the product and the price offered does not give satisfaction to partners which results in low partner loyalty. This study aims to determine the effect of product quality and price on partner loyalty through partner satisfaction with the Joker Corporation leker partner in Yogyakarta. The sample in this study amounted to 30 respondents with census sampling techniques. Analysis of the data used in this study is path analysis using SPSS 26, where previously validity tests, reliability tests, cross tabulation analysis, correlation coefficients, coefficient of determination, simple and multiple linear regression analysis, and significance tests (t test and F test ). The results of this study indicate that product quality and price partially have a positive and significant effect on partner satisfaction and partner loyalty. And simultaneously shows that product quality and price have a positive and significant effect on partner satisfaction and partner loyalty. Price variable have a greater influence on partner satisfaction and partner loyalty than product quality variable